2010
DOI: 10.1016/j.jacc.2010.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Prognostic Implications of Improved Assay Performance With a Sensitive Assay for Cardiac Troponin I

Abstract: Low-level increases in cTnI using a sensitive assay identify patients at higher risk of death or MI. These findings support current American College of Cardiology/American Heart Association recommendations defining MI, and the incremental value of newer, more sensitive assays in identifying high-risk patients with ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 34 publications
6
67
1
3
Order By: Relevance
“…The troponin was detected qualitatively when a specimen contains troponin I (cTnI) above the 99th percentile (TnI>0.5ng/ml) method [7][8][9][10] . The total cholesterol (TC), high density lipoproteins cholesterol (HDL), very low density lipoproteins (VLDL), and triacyl glycerol levels (TG) were analyzed, using the kits provided by HUMAN Diagnostics and the low density lipoprotein level (LDL) was calculated using Friedewald formula [11] .…”
Section: Methodsmentioning
confidence: 99%
“…The troponin was detected qualitatively when a specimen contains troponin I (cTnI) above the 99th percentile (TnI>0.5ng/ml) method [7][8][9][10] . The total cholesterol (TC), high density lipoproteins cholesterol (HDL), very low density lipoproteins (VLDL), and triacyl glycerol levels (TG) were analyzed, using the kits provided by HUMAN Diagnostics and the low density lipoprotein level (LDL) was calculated using Friedewald formula [11] .…”
Section: Methodsmentioning
confidence: 99%
“…Previously, Bonaca et al and Apple et al evaluated the prognostic value of high-sensitivity troponin in the setting of chest pain, but did not compare with conventional troponins 7,8 . This comparison is essential to evaluate whether the new assay should replace the old assay.…”
Section: In-hospital Eventesmentioning
confidence: 99%
“…Although preliminary data suggest that high-sensitivity assays have prognostic value 7 , they have (Universal Definition of Infarction) 8 ; (2) electrocardiographic ischemic changes consisting of transient ST-segment depression (≥ 0.05 mV) or T wave inversion (≥ 0.1 mV); (3) previous documentation of coronary artery disease, defined as a definitive history of myocardial infarction or coronary obstruction ≥ 50% at angiography. Once fulfilling criteria for entering the study, patients provided written informed consent.…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation has been substantiated in large studies that have assessed both sensitive and high-sensitivity cardiac troponin assays in both diagnostic and prognostic studies of patients with acute coronary syndromes (ACSs) (2)(3)(4). Moreover, recent data have demonstrated that high-sensitivity cardiac troponin assays can identify individuals at risk for an adverse outcome outside of the ACS setting (5)(6)(7), further supporting the notion that cardiac troponin may be the optimal biomarker for predicting a cardiac outcome.…”
mentioning
confidence: 91%